2000
DOI: 10.1038/sj.onc.1203943
|View full text |Cite
|
Sign up to set email alerts
|

Translin binds to the sequences adjacent to the breakpoints of the TLS and CHOP genes in liposarcomas with translocation t(12;16)

Abstract: Myxoid and round-cell liposarcomas share the translocation t(12;16)(q13;p11) creating the TLS-CHOP fusion gene as a common genetic alteration. We previously reported several unique characteristics of genomic sequences around the breakpoints in the TLS and CHOP loci, and among them was the presence of consensus recognition motifs of Translin, a protein that associates with chromosomal translocations of lymphoid neoplasms. We further extended our search for Translin binding motifs in sequences adjacent to breakp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…In two tumors (cases 2 and 3), the breakpoint sequence showed strong homology to the consensus binding site sequence of Translin. Translin is a protein involved in recombination and translocations, as it not only binds to translocation breakpoint sequences in hematopoietic malignancies but also binds to translocation breakpoints in alveolar rhabdomyosarcomas and liposarcomas (Aoki et al, 1995;Chalk et al, 1997;Hosaka et al, 2000). The degress of homology to consensus Translin-binding sites observed in this study (71 and 75%, respectively) was in accordance to those reported previously in liposarcomas (more than 70%), but higher than those reported in alveolar rhabdomyosarcomas (62%).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In two tumors (cases 2 and 3), the breakpoint sequence showed strong homology to the consensus binding site sequence of Translin. Translin is a protein involved in recombination and translocations, as it not only binds to translocation breakpoint sequences in hematopoietic malignancies but also binds to translocation breakpoints in alveolar rhabdomyosarcomas and liposarcomas (Aoki et al, 1995;Chalk et al, 1997;Hosaka et al, 2000). The degress of homology to consensus Translin-binding sites observed in this study (71 and 75%, respectively) was in accordance to those reported previously in liposarcomas (more than 70%), but higher than those reported in alveolar rhabdomyosarcomas (62%).…”
Section: Discussionsupporting
confidence: 81%
“…The positions of other recombination sequences (heptamer/nonamer, chi consensus, alternating purine/pyrimidine, polypurine or polypyrimidine sequences) were not correlated with those of the junction points. However, using criteria similar to Hosaka et al (2000), we found that the sense sequence at the SYT breakpoint in tumor 3 and the antisense sequence at the SSX1 breakpoint in tumor 2 (Figure 3) had a strong homology (71 and 75%, respectively) to the consensus recognition sequences of Translin.…”
Section: Resultsmentioning
confidence: 99%
“…For example, translin binding sites at, or close to, the breakpoint junctions have been found in the neoplasia-related t(1; 14)(p32;q11), t(2;13)(q35;q14), t(8;14)(q24;q11), t(12;16)(q13;p11), and t(14;18)(q32;q21) (Aoki et al, 1995;Chalk et al, 1997;Kanoe et al, 1999;Hosaka et al, 2000). However, such sequences are very frequent in the human genome (Hosaka et al, 2000), and the presence of binding motifs close to breakpoint junctions may well be fortuitous.…”
mentioning
confidence: 98%
“…For example, translin binding sites at, or close to, the breakpoint junctions have been found in the neoplasia-related t(1; 14)(p32;q11), t(2;13)(q35;q14), t(8;14)(q24;q11), t(12;16)(q13;p11), and t(14;18)(q32;q21) (Aoki et al, 1995;Chalk et al, 1997;Kanoe et al, 1999;Hosaka et al, 2000). However, such sequences are very frequent in the human genome (Hosaka et al, 2000), and the presence of binding motifs close to breakpoint junctions may well be fortuitous. Enzymes have also been implicated, with binding sites for DNA topoisomerases I and II having been identified in inv(10)(q11q11) in thyroid carcinomas (Klugbauer et al, 2001) and in t(9;11)(p22;q23) in therapy-related AML (Felix et al, 1995;Atlas et al, 1998), respectively.…”
mentioning
confidence: 98%
“…It is intriguing that neither the PKA-nor the PKC-mediated signaling pathway contributes to this rescue effect of the A 2A -R. Instead, a novel A 2A -R-interacting protein [the Translin-associated protein X (TRAX) (Aoki et al, 1997)] that binds to the C terminus of the A 2A -R might mediate the rescue effect of A 2A -R. TRAX was originally identified as a binding protein of Translin using a yeast two-hybrid system (Aoki et al, 1997). Translin is a protein that binds RNA and singlestranded DNA with potential functions in DNA rearrangement and repair, mitotic cell division, mRNA transport, and translational regulation (Aoki et al, 1995(Aoki et al, , 1997Han et al, 1995;Wu et al, 1997;Hosaka et al, 2000;Ishida et al, 2002;Yang et al, 2003). TRAX is a 33-kDa protein whose amino acids have 28% identity to those of Translin (Aoki et al, 1997).…”
mentioning
confidence: 99%